MAPPING TAXPAYER AWARENESS RESEARCH : A BIBLIOMETRIC STUDY USING VOSVIEWER - Atik Sayyidatul Islamiyah; Sri Andriani (Yurisprudentia: Jurnal Hukum Ekonomi, 2025)
This study aims to map the development of research on taxpayer awareness using a bibliometric approach with the aid of VOSviewer software. Data were collected from Google Scholar for the period 2019–2024 and analyzed using Publish or Perish, Mendeley, and VOSviewer. Dominant themes, key keywords, and the structural relationships between concepts in the relevant literature were identified through analysis. The mapping results revealed seven main clusters covering topics such as individual and corporate tax compliance, the role of education, sanctions, and the quality of tax services. Network visualization shows strong connections between taxpayer awareness, individual taxpayer compliance, corporate taxpayer compliance, tax sanctions, and socialization. Additionally, this study found that there is limited research on aspects of digitalization and psychological strategies in relation to taxpayer awareness. Consequently, this study not only provides a comprehensive overview of how the topic has evolved but also offers new research opportunities relevant to current policy needs. The findings are expected to serve as a foundation for the development of more inclusive, service-oriented, and improvement-focused tax policy strategies.